IMPLEMENTASI ETIKA BISNIS MOBILE MARKETING RESELLER FASHION: PERSPEKTIF SEBAGAI PENJUAL DAN KONSUMEN - Sofeyana Sofeyana; Teguh Widodo (Inovbiz: Jurnal Inovasi Bisnis, 2015)
Abstract: This study aims to determine the extent of the application of business ethics conducted by mobile marketing reseller of basic fashion as customer purchase decision. The type of research is descriptive, The data were collected from 8 (eight) respondents and they were the mobile marketing principals through  the  interview  processes.  These  results  indicate  that  the  reseller business fashion in general has been implementing business ethics. because the transaction was not occured by face to face but in online then business ethics which should be applied in mobile marketing from the perspective as the seller and the consumer are included contact person, responding to consumer curiosity, honest and responsible of reseller fashion, setting the price that corresponding market price, providing good service, providing a sense of satisfaction for consumers. While the form of the application of business ethics reseller fashion as consumers are: creating a purchase decision quickly, attitude response from consumers and fulfilling promises. Keywords : Business Ethics, Mobile Marketing, Reseller Fashion